Legal Provisions For Hospital Services: Ensuring Accessible and Affordable Healthcare Services: The Role of Legal Provisions (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Hospitals, being one of themost important components within the national health systems, have graduallychanged their roles to respond to community needs and reach them through itslinkages with primary health care. The best health services are those that areeasily accessible, both time wise and distance wise to all classes of society,those that can be afforded by the society and government which provides themand affordable by people who utilize them, of a minimum acceptable standard inkeeping with the need of the users at each level, available to all classes ofsociety who need them, and which range in their coverage from womb to tomb,with effective deployment of available resources.